Enhancing student visualization of primary stabilizing forces through 3D protein models - Flynn, Aine, author (Colorado State University. Libraries, 2024)
This Honors Thesis is an action-research project which involves creative design of a lesson plan for a Principles of Biochemistry course, aimed at making the challenging topic of protein structure more visual, engaging, and digestible. Action-research projects systematically test new practices, using collection of data as an evaluation of the effectiveness of the new practice. By combining scientifically accurate content with immersive pedagogy strategies, this thesis project explores how 3D protein models can enhance student understanding of primary stabilizing forces within protein structures. In contrast to traditional lecture-style lessons, this project tests if non-traditional pedagogical strategies improve student learning and performance. The lesson plan being tested consists of two parts: (1) guided-instruction construction of a 3D protein model, and (2) a corresponding worksheet. The lesson plan was taught in a flip-style class, in which students were instructed to watch the Echo360 recording of Dr. Sholder's traditional lecture on protein structure. The goal was for students to come to class with some context on the lecture material, before applying the content to an interactive activity during class. During class, students independently constructed their own 3D protein model, while following along with prompts on the corresponding worksheet. The physical protein model adapted Dr. Sholder's 2D representation of a protein (the helical wheel diagram) into a 3D model aimed at enhancing students' visuospatial understanding of molecular interactions. The goal was to help students better understand the learning objective: Compare and contrast the interactions driving the formation of secondary, tertiary, and quaternary structure of proteins. During project implementation– when the lesson plan was taught– students were instructed to construct the model, answer prompts on the worksheet, and answer iClicker "checkpoints" aimed at evaluating student comprehension at each level of protein structure. iClicker data indicated that over half the class benefitted from the lesson plan and interactive 3D protein model. However, more research is necessary to determine the effectiveness of the lesson plan. Some considerations in this project are time management, assessment/evaluation tools, and the flexibility of materials. Overall, this project offers a number of benefits for myself, people in my field, and people outside of my field.
Colorado State University. College of Natural Sciences, Biological Sciences Department. Colorado State University Honors Program.
Zip file contains: worksheet set 1 for instructors; worksheet set 2 for students; worksheet key; presentations in pdf and mp4 formats.
To request a transcript for the video, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: visuospatial; biochemistry; protein; structure; folding; pedagogy; lesson plan; visualization; stabilizing forces